Genotype/Phenotype correlation and prognosis for undescribed ACTC1 missense variants. (25th November 2020) - Cicerchia, M.N; Ochoa, J.P; Cardenas-Reyes, I; Fernandez Ferro, G; Brogger, M.N; Fernandez, X; Garcia Hernandez, S; Garcia, D; Salazar Mendiguchia, J; Ortiz, M; Monserrat, L
Abstract: Purpose: Establish the genotype/phenotype correlation for missense undescribed variants in ACTC1, and evaluate their prognostic implications. Methods: A systematic screening for the ACTC1 gene was performed using NGS in 17, 683 individuals with inherited cardiovascular disease, 6, 984 of them with hypertrophic cardiomyopathy, 3, 507 with dilated cardiomyopathy, and 760 left ventricular non-compaction. These phenotypes were clinically diagnosed by each center prior to the genetic study. Frequency of the variants was compared with gene gnomAD and ClinVar databases. A systematic review of the literature was performed to search for previously reported variants. We evaluated available follow up data and constructed Kaplan-Meier survival curves free from cardiovascular death (sudden death, Heart transplant, heart failure death, appropriate ICD discharge and stroke related death). Log-rank test was used to compare event-free survival time between males and females. Results: 39 missense variants were identified in 283 carriers (125 index cases; 158 first-degree relatives). Twenty-two have not been previously described or identified in public databases. 17 have been reported in gnomAD or Clinvar. Carriers phenotypes were: 120 HCM; 43 LVNC; 16 DCM; three had cardiac septal defect and two had sudden death. Some of the carriers had overlapped or combined phenotypes: 7 HCM and LVNC, 7 septal defects and LVNC, 3 HCM and septal defects, 4 MCD and LVNC. 24 were healthy carriers, and we have no phenotypic data of the remaining individuals. Family studies were performed in 12 families out of the 22 undescribed variants, showing cosegregation in 8 variants. One case was "de novo". Interestingly, a rare variant, previously identified as VUS in ClinVar, showed a clearly cosegregation with HCM. The Leu10Met variant with a frequency of 9/282084 alleles in gnomAD (1/15671 individuals) was identified in 20 index cases, which represents 1/884 of all the genotyped (0.11%), and 1/387 patients with HCM (0.35%). We found it in 2/9289 patients with other phenotypes (p<0.001). 51 patients (18%) presented an event during follow up. In several cases, carriers developed early atrial fibrillation. The survival curve shows adverse events from the first decade of life, with a 10% cumulative rate of events at age 40, 80% survival at age 60, and a 60% survival at age 70. No significant differences in the incidence of cardiovascular death between men and women were observed. Conclusion: HCM is the most frequent phenotype in carriers of ACTC1 variants, followed by LVNC, and DCM. Septal defects are not rare, and they are usually described in combination with cardiomyopathies. Disease course seems to have a good prognosis. Sudden death is an exception at early ages and appears to be associated with severe morphological expression. Given the presence of cosegregation with disease in rare variants, many of the ACTC1 variants may have an incomplete penetrance, and late disease expression. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Health in Code